Middle term optimal control problem in eutrophic lakes through advanced mathematical programming approaches - Estrada, Vanina Gisela (2009)
In this work, we address lake biorestoration through the formulation of first principles models for water quality and advanced mathematical programming techniques. Dynamic mass balances have been formulated on main phytoplankton groups and nutrients, as well as other components available in lakes and reservoirs. Main parameters in the model have been estimated in previous work Estrada et al., 2008. The combined reductions in nutrient loading and inlake biorestoration strategies to control algae growth and reduce eutrophication have been formulated as an optimal control problem for a middle term time horizon (thr ee years). The problem has been formulated within a simultaneous optim ization framework and solvin g the large scale nonlinear program with an Interior Point method (Biegler et al., 2002). Numerical results give deep insight on the quantitative application of restoration strategies.